Impact of hospitalization for checking medication adherence due to resistant and refractory hypertension suspicious on short and mid-term blood pressure control. (25th November 2020) - Pio-Abreu, A; Trani-Ferreira, F; Silva, G.V; Bortolotto, L.A; Drager, L
Abstract: Background: Resistant (HR) and refractory hypertension (HRef) are associated with increased cardiovascular events and target-organ damage. However, appropriate HR and HRef diagnosis require good drug adherence. In this context, the "gold standard" method for assessing adherence is supervised medication intake. However, it is not clear the real utility of supervised medication intake in clinical practice. Purpose: To evaluate whether hospitalization for confirming anti-hypertensive adherence in patients with HR and HRef may impact blood pressure (BP) control after hospital discharge in patients with HR or HRef suspicious at a tertiary outpatient clinic. Methods: We recruited consecutive patients with HR or HRef suspicious admitted to the Hospital for confirming treatment adherence. HR was defined as uncontrolled office BP (≥140 and/or ≥90mmHg) despite using ≥3 classes at optimal doses (one of them being diuretic) or controlled BP using ≥4 classes. HRef was defined as no BP control despite using ≥5 antihypertensive drugs. Patients with suspected HRef who did not meet the criteria but full field the HR definition were named HRNoRef. During hospitalization, all patients used low sodium diet and had supervised taking of prescribed drugs by the medical team aiming BP control. We defined not only the rate of adherence and HF/HRef status but also BP and number of antihypertensive drugs at hospital discharge and in the two first return outpatient's visits. Results: We studied a total of 83 patients with suspected HR/HRef (age 53±14 years; 76% females; pre-hospitalization systolic and diastolic BP: 177±28 and 106±21mmHg, respectively). Of these, 68.7% (57 patients) had suspected HRef in the outpatient clinic. The average number of antihypertensive drugs on admission was 5.3±1.3 classes. After hospitalization, the overall frequency of HR fell to 80% (66 patients). The average number of antihypertensive drugs at hospital discharge as well as systolic and diastolic BP was 4.5±1.3 classes, 131±17mmHg and 80±12mmHg, respectively (p<0.001 vs. pre-hospitalization for all comparisons). Among the HR types, HRef was confirmed in only 27 patients (32.5%). During the outpatient follow-up, the patients remained with lower number of antihypertensive drugs as well as lower systolic and diastolic BP at first outpatient visit (mean returned time: 2.1±1.7months) and second outpatient visit post-discharge (mean returned time 7.1±2.6months) as compared to pre-hospitalization data: First visit: 4.3±1.2 classes, systolic: 152±24mmHg, diastolic BP: 89±17mmHg; second visit: 4.5±1.3 classes, systolic: 150±26mmHg, diastolic BP: 89±15mmHg; (p<0.001 vs. pre-hospitalization for all comparisons). Conclusion: Supervised medication intake during hospitalization may help not only to define the HR and HRef status but also to have impact on the number of antihypertensive drugs and lower BP values at short and mid-term follow-up. Funding Acknowledgement: Type of funding source: None